Characterization of pseudomonas aeruginosa from hospital sewage water and nearby community water based on their multi-drug-resistant gene - Adiba, Rezwana Afrin; Ferdous, Riyan Mehzabin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.